Active Targeting Gold Nanoparticle for Chemotherapy Drug Delivery: A Review - Azhoma Gumala; Sutriyo Sutriyo (Tabriz University of Medical Sciences, 2022)
Active targeting strategy in chemotherapy drug delivery aims to improve the therapeutic outcomes and minimize the side effects of chemotherapeutics. This review discusses utilizing ligands attached to gold nanoparticles (AuNPs) along with several specific ligands attached to AuNPs for active targeting in chemotherapy drug delivery. Antibodies, peptides, vitamins, DNA, polysaccharides, aptamers, and hormones showed active-targeting abilities as ligands attached to AuNPs. Active-targeting AuNPs enhanced cellular uptake and cytotoxicity in a specific cancer cell in vitro while reducing tumor growth in vivo by improving the photothermal, photodynamic and chemotherapy effects. Active-targeting ligands increased the internalization of AuNPs loaded onto the specific tumor site and minimized the accumulation in the normal site. AuNPs with active-targeting ligands such as antibodies, peptides, vitamins, DNA polysaccharides, aptamers, and hormones can improve the therapeutic outcomes of chemotherapeutics and can attenuate the toxicity effect in normal cells. For further research and development, researchers should be addressing AuNP characterization, drug-ligand disposition, active-targeting AuNP quantification, and target-AuNPs pertinence concerning the desired therapeutic outcomes.